Effects of dietary w-3 fatty acids content on productive performances and meat quality of Martina Franca donkey foals - Pinto, F.; Schiavone, M.; Marsico, G. (Progress in Nutrition, 2015)
To investigate the effect of diets containing fatty acids of the w-3 series on productive traits, on carcass cut composition, on meat chemical composition as well as on meat fatty acid composition, eight Martina Franca donkey foals were utilized. The animals, weaned at 8 months of age, were divided into two groups of 4 subjects each, homogeneous for age and live weight. The first group (control) was given wheat straw and a complete feed non supplemented with w-3; the second (trial) was given wheat straw and a w-3 supplemented complete feed. All the animals were slaughtered after 138 days of trial. From the collected data, it emerges that the utilization of w-3 enriched feed, even though with different levels of statistical significance (P ² 0.05 and/or P ² 0.01), determines differences in the content of fat, meat and bone of shoulder and loin and in the meat ashes percent. As regards the meat fatty acids distribution, no remarkable differences are observed as to the saturated series, whereas the unsaturated one (P² 0.05) seems to increase the content of C18:3w3 (ALA - a-linoleic), of C22:5w3 (DPA – docosapentenoic acid), of C22:6w3 (DHA – docosahesanoic acid) and of UFA, PUFA and total w-3 acids.